2008
DOI: 10.1093/pubmed/fdn001
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of casualty and NHS Direct use

Abstract: Reduced access to A&E services will disproportionately affect poorer individuals, whereas increased investment in telephone services will benefit affluent populations. Current national policy may widen inequities in access to emergency care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 13 publications
6
47
1
Order By: Relevance
“…In contrast to reports of declined telephone health service use among minority ethnic groups [39][40][41] , the foreign-born participants in the present study seemed to be using the service frequently and had contacted SHD without hesitation. The desires of the foreign-born participants regarding a pronounced dialogue are likely to benefit all callers and increase service accessibility.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to reports of declined telephone health service use among minority ethnic groups [39][40][41] , the foreign-born participants in the present study seemed to be using the service frequently and had contacted SHD without hesitation. The desires of the foreign-born participants regarding a pronounced dialogue are likely to benefit all callers and increase service accessibility.…”
Section: Discussioncontrasting
confidence: 99%
“…Perspectives of gender and power can be intertwined with social differentiations such as ethnicity, class, sexuality, age and dis/ability, often denominated intersectionality [27] . For example, having a deprived socioeconomic situation, belonging to a minority ethnic group [39][40][41] or being aged above 65 [40] play a part in decreased use of telephone health services (the latter in contrast to 65+ patients' increased use of general practice care services [40] ).…”
mentioning
confidence: 99%
“…This parallels results from the UK regarding NHS Direct, [18,19] indicating that migrants use this service less. Our study has also shown that the patients who turned to the telenursing services were predominately young (mean age for women 29 years and for men 33 years).…”
Section: Discussionsupporting
confidence: 76%
“…[14][15][16] It has also been reported that gender interact (or intersect) with other categories, such as age and ethnicity in people's health behaviour. For example, studies on NHS Direct in the UK [18,19] have indicated that migrants use this service less. Sweden has for several decades been a multicultural society.…”
Section: Introductionmentioning
confidence: 99%
“…Telephone contact is used variably for assessment and triage of acute problems; [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] general practice consultations; [34][35][36][37][38][39][40] to offer health education; 41,42 and to offer support for those with chronic illness 43,44 or those in need of palliative care. 45 The literature on telephone consultations consists largely of small and heterogeneous primary studies, most of which had practical challenges or methodological flaws.…”
Section: Telephonementioning
confidence: 99%